Predicting non-axisymmetric growth and facet evolution during lithiation of crystalline silicon anode particles through orientation-dependent interface reaction. (15th June 2023) - Bhowmick, Amit; Chakraborty, Jeevanjyoti
Abstract: A finite deformation modeling framework is developed to capture the experimentally observed two-phase, non-axisymmetric growth during the first lithiation of crystalline silicon cylinder in an improved fashion. The key feature of this model is an orientation-dependent interface reaction constant. Furthermore, the migration of lithium through the lithium-rich, growing amorphous zone is modeled through two additional features. First, an alloying–dealloying reaction that distinguishes between "movable" and "immovable" lithium parts. Second, a strong two-way coupling between diffusion and stress in contrast to existing mathematical models of non-axisymmetric growth. These features enable the prediction of a non-uniform distribution of concentration and stresses. The most important ability of this framework is that it can capture the evolution of facets at the crystalline–amorphous interface shown in experimental studies. The ensuing orientation-dependent interface velocity breaks the axisymmetric shape of the nanowire despite the initial circular geometry and the maintenance of an axisymmetric lithium influx. A very interesting finding is that the deposition of lithium and induced stresses are higher at the sites with lower interface velocity, which occur at the junction of two facets. The resulting stress concentration, in turn, pushes towards the further accumulation of lithium at those sites. It is expected that the improved modeling capabilities of this framework will contribute a step in moving beyond the limitations of simplistic structural design of lithium-ion battery particles. Highlights: Modeling of non-axisymmetric growth of crystalline silicon anode particle. Alloying–dealloying reaction incorporated in growing amorphous zone. Non-axisymmetric growth despite circular geometry and axisymmetric influx. Non-axisymmetry captured through orientation-dependent interface reaction. Model captures experimentally-observed facet evolution.